Relationships among prices of rubber in ASEAN: Bayesian structural VAR model - N. Kaewsompong (2018)
© 2016 by the Mathematical Association of Thailand. All rights reserved. International rubber markets are seen to be volatile due to the high competitiveness between major rubber export markets. This paper analyses the causal impact price transmission among ASEAN over the period of 2008 to 2015. The Bayesian structural VAR model is conducted to analyse relationship among rubber export price for top four rubber producing in ASEAN. We considered the varying sets of hyper-parameters to obtain the best fit model. The results reveal that Indonesia and Thailand have more efficiency when it comes to adjustment of their rubber prices than Malaysia and Vietnam.